2010
DOI: 10.1143/jjap.49.121302
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Sputtered Silicon Thin Films after Rapid Thermal Annealing for Active-Matrix Organic Light Emitting Diode

Abstract: The microcrystalline phase obtained by adopting a two-step rapid thermal annealing (RTA) process for rf-sputtered silicon films deposited on thermally durable glass was characterized. The optical properties, surface morphology, and internal stress of the annealed Si films are investigated. As the thermally durable glass substrate allows heating of the deposited films at high temperatures, micro-polycrystalline silicon (micro-poly-Si) films of uniform grain size with a smooth surface and a low internal stress c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The number of Ar inclusion in the film is speculated to be reduced by adjusting the pressure. 16,17) Then, Si films were deposited on PI substrates under the condition of 7 mTorr pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The number of Ar inclusion in the film is speculated to be reduced by adjusting the pressure. 16,17) Then, Si films were deposited on PI substrates under the condition of 7 mTorr pressure.…”
Section: Resultsmentioning
confidence: 99%
“…RTP or rapid thermal annealing (RTA) allows the nucleation process to occur at temperatures near the melting point of Si without melting the Silica glass substrate. It is well demonstrated that the nucleation rate is low near the melting point of Si; hence grain sizes obtained with RTA are generally larger [27,28].…”
Section: Recrystallization and Annealing Of Deposited Si Thin Filmsmentioning
confidence: 99%